Diacylglycerol Acyltransferase1 gene polymorphism and its association with milk fatty acid components in Holstein Friesian dairy cattle - Asmarasari, Santi Ananda; Sumantri, Cece; Mathius, I Wayan; Anggraeni, Anneke (Indonesian Animal Sciences Society, 2014)
Diacylglycerol acyltransferase 1 (DGAT1) gene is one of the major genes that has an important role in milk fat synthesis. This research was aimed at to identifying genetic polymorphism of the DGAT1 gene by PCR-RFLP method and its association to milk fatty acid components. Â Animals studied were Holstein Friesian (HF) cattle from BBPTU Baturraden (123 cows) and BPPT SP Cikole (36 cows). The length of PCR product of the DGAT1gene was 411 bp. Genotyping resulted in two types of alleles, namely K (411 bp) and A (203 and 208 bp); and two genotypes, namely KK (411 bp) and AK (203, 208 and 411 bp). For both locations, genotype frequency of AK (0.75) was higher than KK (0.25). The allele frequency of K (0.64) was higher than A (0.36). Heterozygosity of HF cattles at both locations was relatively high (Ho>He). The DGAT1 gene of the observed HF cattle was polymorphic. Result showed that there was an association between the DGAT1 polymorphism with unsaturated fatty acids especially in nervonat acid. The AK cows had a significant effect on unsaturated fatty acid content of which having a higher nervonat content (0.05%) (P<0.05) than that of the KK cows (0.03%). From the results, it is concluded that the DGAT1 gene can be functioned as a marker of selection for milk fatty acids. Key Words: DGAT1, PCR-RFLP, Holstein Friesian, Fatty Acids